2015
DOI: 10.1155/2015/264971
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Induces DNA Damage Whereas Isoflurane Leads to Higher Antioxidative Status in Anesthetized Rats

Abstract: Taking into account that there are controversial antioxidative effects of inhalational anesthetics isoflurane and sevoflurane and absence of comparison of genotoxicity of both anesthetics in animal model, the aim of this study was to compare DNA damage and antioxidant status in Wistar rats exposed to a single time to isoflurane or sevoflurane. The alkaline single-cell gel electrophoresis assay (comet assay) was performed in order to evaluate DNA damage in whole blood cells of control animals (unexposed; n = 6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 45 publications
0
25
0
1
Order By: Relevance
“…In this study, the use of isoflurane is a potentially confounding factor because it is thought to have antioxidant effects in and of itself (6267). This claim is somewhat controversial, however, with other studies showing a prooxidant effect of isoflurane (6267). The experiments performed herein were not designed to resolve this conflict.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the use of isoflurane is a potentially confounding factor because it is thought to have antioxidant effects in and of itself (6267). This claim is somewhat controversial, however, with other studies showing a prooxidant effect of isoflurane (6267). The experiments performed herein were not designed to resolve this conflict.…”
Section: Discussionmentioning
confidence: 99%
“…We have found a significant increase in the S-phase duration of the neural progenitors exposed to sevoflurane (Figures 5(f) , 5(g) , and 5(h) ), further indicating the downregulation of differentiation in the fetal PFC. The S-phase duration is the main time for neural progenitors to control the quality of replicated DNA [ 27 ], and sevoflurane has been reported to significantly increase DNA damage in rodents [ 42 ]. Therefore, our observation of prolonged S-phase may also indicate that DNA replication of neural progenitors in the sevoflurane group is abnormal, pending further study.…”
Section: Discussionmentioning
confidence: 99%
“…Rocha et al (35) provided evidence that sevoflurane induced genetic damage, whereas isoflurane increased systemic antioxidative status in Wistar rats exposed for 120 min. They suggest that possible mechanisms of sevoflurane genotoxicity include direct genotoxicity and/ or oxidative route by metabolism (35). Clinical studies indicated the absence of systemic DNA damage or oxidative DNA damage in patients under isoflurane anaesthesia (33).…”
Section: Discussionmentioning
confidence: 99%
“…Hirata et al (37) proved that isoflurane reduced myocardial infarction size by modulating mitochondrial ROS at clinical concentrations. Rocha et al (35) showed that rats anesthetised with isoflurane had a higher plasma antioxidative status. Concerning these findings, we presume that repair of DNA in rats treated with isoflurane in our study could be the consequence of the activation of antioxidative mechanisms in kidney cells.…”
Section: Discussionmentioning
confidence: 99%